2013
DOI: 10.1016/j.ijcard.2011.11.032
|View full text |Cite
|
Sign up to set email alerts
|

MASP-2 activation is involved in ischemia-related necrotic myocardial injury in humans

Abstract: Background/Objectives Insufficient blood supply to the heart results in ischemic injury manifested clinically as myocardial infarction (MI). Following ischemia, inflammation is provoked and related to the clinical outcomes. A recent basic science study indicates that complement factor MASP-2 plays an important role in animal models of ischemia/reperfusion injury. We investigated the role of MASP-2 in human acute myocardial ischemia in two clinical settings: (1) Acute MI, and (2) Open heart surgery. Methods A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 46 publications
3
27
0
Order By: Relevance
“…Peripheral blood cTnI levels increased significantly following cardiac surgery compared with the immediate pre-surgery values (Table 2), consistent with previous literature [7, 8, 81]. A univariate analysis showed that coronary Bb levels immediately after release of AXCL directly correlated with post-surgical peripheral blood cTnI levels (Spearman’s rho correlation coefficient = 0.465, P < 0.01; Fig 5a).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Peripheral blood cTnI levels increased significantly following cardiac surgery compared with the immediate pre-surgery values (Table 2), consistent with previous literature [7, 8, 81]. A univariate analysis showed that coronary Bb levels immediately after release of AXCL directly correlated with post-surgical peripheral blood cTnI levels (Spearman’s rho correlation coefficient = 0.465, P < 0.01; Fig 5a).…”
Section: Resultssupporting
confidence: 89%
“…The lectin pathway can recognize these antibody-neoantigen complexes and appears to be the dominant pathway of C3 activation [73, 81, 105]. C3 activation is then amplified in a fB-alternative pathway-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, 29 patients with acute MI had significantly lower MASP-2 levels compared with 50 healthy individuals, or 27 patients with coronary artery disease (CAD) but without acute MI [33]. Lower MASP-2 levels were also found in 81 patients after cardiac surgery with cardiopulmonary bypass compared with before surgery, and it was suggested that reduction of MASP-2 levels was caused by complement activation during myocardial ischaemia [33]. In a study in 135 patients with acute stroke, MASP-2 levels were measured on days 0-4, 7 and 90, but showed neither any significant changes over time, differences between ischaemic (n = 109) and haemorrhagic stroke (n = 26), nor any association with clinical outcome [34].…”
Section: Introductionmentioning
confidence: 96%
“…These patients had significantly lower MASP-2 levels at admission compared with 256 patients without cardiovascular events, but after adjustment for risk factors MASP-2 was not an independent predictor of cardiovascular events [32]. In another study, 29 patients with acute MI had significantly lower MASP-2 levels compared with 50 healthy individuals, or 27 patients with coronary artery disease (CAD) but without acute MI [33]. Lower MASP-2 levels were also found in 81 patients after cardiac surgery with cardiopulmonary bypass compared with before surgery, and it was suggested that reduction of MASP-2 levels was caused by complement activation during myocardial ischaemia [33].…”
Section: Introductionmentioning
confidence: 98%
“…In a cohort study of individuals with T2DM, MASP-2 levels were significantly decreased in patients with acute cardiovascular events (Mellbin et al, 2012). MASP-2 levels were also lower in another study in patients with acute MI (Zhang et al, 2013). These first data suggest that MASP-1 and MASP-2, both of which interact with coagulation, are altered in patients with acute cardio-and cerebrovascular diseases.…”
Section: Masps In Cardiovascular Diseasesmentioning
confidence: 82%